TorakochirurgiaProsthesis implanted in pleural cavity post pneumonectomy imitating neoplastic tumor – case report - Religioni, Jarosław; Orłowski, Tadeusz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2006)
We present the case of a 57-year-old patient with a huge tumour of the right pleura. The patient had been operated on due to TBC 47 years ago. During thoracotomy the lesion turned out to be an implanted surgical prosthesis.